Investigation of electrophysical properties of nanomodified fireproof EVA polymer compositions - Chulieieva, Olena (Technology audit and production reserves, 2018)
The object of research is the electrophysical properties of fireproof composite materials of ethylene with vinyl acetate, which include filler-flame retardants and modifiers. One of the biggest problems is the change in the electrophysical properties of fireproof composite materials, depending on the chemical properties and dispersion of fillers, fire retardants and modifiers. In order to solve this problem, the dependence of electric strength, specific volume electrical resistance, permittivity and tangent of dielectric loss angle on the number of modifiers and properties of ingredients of polymer compositions is investigated. A copolymer of ethylene with vinyl acetate is used as well as methods for determining the electrical strength, electrical bulk resistance, dielectric loss tangent, permittivity. The results show that the dielectric strength significantly increases to 32-35 kV/mm in the case of use as fillers-flame retardants of aluminum oxide trihydrate with a smaller average particle diameter of the EVA-1-based polymer matrix and modifier 1. When using the EVA-2-based polymer matrix, high rates (41 kV/mm) obtained for compositions with hydromagnesite and modifier 2. The specific volume electrical resistance varies little for modified polymer compositions using magnesium oxide dihydrate with a smaller average particle size and modifier 2, as well as for the EVA-1 and EVA-2 polymer matrices. After exposure to moisture, the specific volume electrical resistance has a maximum value of 1.2∙1013 Ohm∙cm for the EVA-1-based polymer composition, a flame retardant – aluminum oxide trihydrate and modifier 1. The permittivity and dielectric loss tangent have the best performance for EVA-1-based polymer compositions, hydromagnesite and modifier 2 (ε=3.3; tg=6∙10-3). This makes it possible to increase the electrical properties of fireproof compositions for the manufacture of insulation and cable sheaths compared with similar known materials, this reduces material consumption by reducing thickness and makes it possible to increase the economic efficiency of production of fire-resistant cables.